2015
DOI: 10.1186/s13148-015-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

The placenta: phenotypic and epigenetic modifications induced by Assisted Reproductive Technologies throughout pregnancy

Abstract: Today, there is growing interest in the potential epigenetic risk related to assisted reproductive technologies (ART). Much evidence in the literature supports the hypothesis that adverse pregnancy outcomes linked to ART are associated with abnormal trophoblastic invasion. The aim of this review is to investigate the relationship between epigenetic dysregulation caused by ART and subsequent placental response. The dialogue between the endometrium and the embryo is a crucial step to achieve successful trophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 187 publications
3
72
0
2
Order By: Relevance
“…DNA methylation on cytosines (5-methylcytosine: 5meC) is an essential epigenetic modification that seems to be particularly affected by in vitro culture (Wright et al ., 2011) and to have an impact on the health of children born after ART, in particular through misregulation of imprinted genes (Fauque et al ., 2007; Choux et al ., 2015), leading to rare syndromes such as Beckwith–Wiedemann and Angelman (Manipalviratn et al ., 2009; Owen and Segars, 2009; Lazaraviciute et al ., 2015). In addition to its importance in imprinting, DNA methylation is involved in the regulation of many developmental processes such as parental imprinting, X-inactivation and control of endogenous retrotransposons (Watkins et al ., 2008b; Corry et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation on cytosines (5-methylcytosine: 5meC) is an essential epigenetic modification that seems to be particularly affected by in vitro culture (Wright et al ., 2011) and to have an impact on the health of children born after ART, in particular through misregulation of imprinted genes (Fauque et al ., 2007; Choux et al ., 2015), leading to rare syndromes such as Beckwith–Wiedemann and Angelman (Manipalviratn et al ., 2009; Owen and Segars, 2009; Lazaraviciute et al ., 2015). In addition to its importance in imprinting, DNA methylation is involved in the regulation of many developmental processes such as parental imprinting, X-inactivation and control of endogenous retrotransposons (Watkins et al ., 2008b; Corry et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, epigenetic changes have been found to play an important role in the regulation of placentation [18]. During pre-implantation embryo development, global DNA methylation reprogramming occurs, and both rodent and choriocarcinoma cell line studies have shown that specific patterns of methylation are important for normal placental function and that aberrations in methylation negatively affect placentation [1921]. …”
Section: Introductionmentioning
confidence: 99%
“…The placental epigenome plays a vital role that could constitute a major compensatory mechanism in the development and adaptive function to environmental stress caused by IVF (Choux et al, ; Decato et al, ). Future studies should focus on the epigenetic mechanisms underlying IVF‐induced regulation of the expression of the imprinted gene H19‐IGF2 as well as histone modification and lncRNA adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on the epigenetic mechanisms underlying IVF‐induced regulation of the expression of the imprinted gene H19‐IGF2 as well as histone modification and lncRNA adjustment. Epigenetic regulation controls transcription at two levels: direct control of DNA through DNA methylation or hydroxymethylation and histone modification of proteins around which DNA is wrapped to constitute nucleosomes (Choux et al, ). We used quantitative BSP to evaluate the methylation status of the H19‐ICR region and found that the total methylation level at CpG dinucleotide sites was remarkably increased in the IVF group.…”
Section: Discussionmentioning
confidence: 99%